2005
DOI: 10.2224/sbp.2005.33.1.57
|View full text |Cite
|
Sign up to set email alerts
|

The Universality of Relationship Characteristics: A Cross-Cultural Comparison of Different Types of Attachment and Loneliness in Canadian and Visiting Chinese Students

Abstract: In this study we investigated the universality of loneliness and attachment in family, romantic, and social relationships by comparing Canadian home students with Chinese visiting students. A total of 223 students completed measures assessing peer, parent, and romantic attachment, and emotional and social loneliness. The results revealed significant main effects of culture and gender for both attachment and loneliness, as well as a significant 2-way interaction for family loneliness. The findings support the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 27 publications
3
27
0
Order By: Relevance
“…Armsden and Greenberg 1987). We expected significant associations between parent and peer attachment, with individuals highly attached to their parents more likely to report a strong attachment also to their peers (Armsden and Greenberg 1987;Di Tommaso et al 2005;Laible 2007;Nada Raja et al 1992;Wilkinson 2004). In line with the literature, we hypothesized significant gender differences on peer attachment, with females being more attached to their peers than their male counterparts (e.g., Gullone and Robinson 2005;Henrich et al 2001;Nada Raja et al 1992;Nelis and Rae 2009;Richards et al 2010;Ruijten et al 2011;Song et al 2009;Sund and Wichstr脴m 2002).…”
Section: The Present Studymentioning
confidence: 58%
See 1 more Smart Citation
“…Armsden and Greenberg 1987). We expected significant associations between parent and peer attachment, with individuals highly attached to their parents more likely to report a strong attachment also to their peers (Armsden and Greenberg 1987;Di Tommaso et al 2005;Laible 2007;Nada Raja et al 1992;Wilkinson 2004). In line with the literature, we hypothesized significant gender differences on peer attachment, with females being more attached to their peers than their male counterparts (e.g., Gullone and Robinson 2005;Henrich et al 2001;Nada Raja et al 1992;Nelis and Rae 2009;Richards et al 2010;Ruijten et al 2011;Song et al 2009;Sund and Wichstr脴m 2002).…”
Section: The Present Studymentioning
confidence: 58%
“…For what concerns the specific interconnections between parent and peer attachment, consistent evidence suggests that parent-child attachment is related to friend attachment (e.g., Armsden and Greenberg 1987;Di Tommaso et al 2005;Laible 2007;Nada Raja et al 1992). For example, Wilkinson (2004) noted that the quality of the attachment relationship established between adolescents and their parents tends to influence the quality of peer attachment relationships that they form.…”
Section: Peer and Parent Attachment Relationshipsmentioning
confidence: 99%
“…Possible difference between the culture a person belongs to and the culture he actually is in as well as different social pressure, direction instruments, physical and characteristic features in those cultures show that it would not be that correct to analyze those tackled concepts by isolating them from the culture. Similarly, researchers like Goodwin, Cook, & Yung, (2001), Cao & Su, (2007), Wood, (2007, Bluigte, (1991), Rokach and Bacanli, (2001), Rokach and Neto, (2000), Ditommaso et al (2005) have emphasized that loneliness being in the first place in regards to absorption and dependency culture and cultural factors are important determinants and these feelings can surface in different ways. As a result, it is possible to say that when the cause effect relation between these three variables is taken into account both of the second and the fourth hypotheses are important and depending on the cultural differences one may one step come forward than the other.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…In the midst of complex and diverse information available from the Western literature and scales of loneliness, measuring loneliness with a cross-culturally developed scale is appropriate to preempt cultural bias. As the literature shows that the difference between individualistic and collectivistic cultures is almost undeniable in several areas like social interaction, social networks, social supports, attachments, self-concept and the like, it is very important to identify culture-free items to measure the experience of loneliness (Hofstede 1980;DiTommaso et al 2005). There is a recent rising trend in individualism/ collectivism in cross-cultural psychology according to Kagitcibasi (1997).…”
Section: Cultural Environment and Loneliness Measurementmentioning
confidence: 99%
“…If the measurement of loneliness is to be cross-cultural, then the loneliness items of UP Loneliness Assessment Scale derived from an international and multicultural sample would satisfy the psychologists from Western cultures who increasingly recognize that many of the assumptions underlying the way they describe and study people may not apply in describing people from non-Western cultures (Church 2001; Kanagava et al 2001) and that people's experiences are culturally rooted. DiTommaso et al (2005) observed from their cross-cultural study that the universality of loneliness exists, but the expression or intensity of the experience may differ among cultures. It is in this context the development of UP Loneliness Assessment Scale would drive researchers and practitioners to employ it as a useful diagnostic tool in dealing with and in the study of loneliness.…”
Section: Discriminant Validitymentioning
confidence: 99%